Industrial energy efficiency and competitiveness - Eichhammer, Wolfgang (UNIDO ViennaAT, 2011)
Analyses the relevance of energy consumption and energy efficiency in the industrial sector of a set of 35 countries. Investigates to what extent countries are presently prepared to absorb energy efficiency technologies and even to develop industries which are capable of producing energy efficient prodocts and processes for the market.